Determinasi Keputusan Pembelian Minyak Goreng Fortune melalui Citra Merek, Kepercayaan Konsumen, dan Word of Mouth - Herman Surijadi; Walter Tabelessy (JoEMS (Journal of Education and Management Studies), 2026)
Purpose: This study aims to analyze the effects of brand image, consumer trust, and word of mouth on the purchasing decisions of Fortune cooking oil consumers in Ambon City. Methodology/approach: This study employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 120 consumers who had purchased and used Fortune cooking oil. The data were analyzed using multiple linear regression with the assistance of Jamovi software. Findings: The findings indicate that brand image, consumer trust, and word of mouth have positive and significant effects on purchasing decisions. Among these variables, word of mouth was found to be the most influential factor affecting consumer purchasing decisions. These findings suggest that purchasing decisions for cooking oil are influenced not only by the functional attributes of the product but also by psychological and social factors reflected in brand perception, consumer trust, and interpersonal communication. Practical implications: The results imply that companies should strengthen brand image, maintain consumer trust, and encourage positive consumer-to-consumer communication to enhance purchasing decisions and sustain consumer preference in a highly competitive market. Originality/value: This study extends consumer behavior research in the context of staple household products by simultaneously examining the effects of brand image, consumer trust, and word of mouth on purchasing decisions for Fortune cooking oil in Ambon City. Unlike previous studies that primarily focused on digital products, smartphones, and retail settings, this study demonstrates that word of mouth is the most dominant factor influencing purchasing decisions in the context of local consumers of household food products.